2018
DOI: 10.1186/s13049-018-0560-8
|View full text |Cite
|
Sign up to set email alerts
|

Initial assessment, level of care and outcome among children who were seen by emergency medical services: a prospective observational study

Abstract: BackgroundThe assessment of children in the Emergency Medical Service (EMS) is infrequent representing 5.4% of the patients in an urban area in the western part of Sweden. In Sweden, patients are assessed on scene by an EMS nurse whom independently decides on interventions and level of care. To aid the EMS nurse in the assessment a triage instrument, Rapid Emergency Triage and Treatment System-paediatrics (RETTS-p) developed for Emergency Department (ED) purpose has been in use the last 5 years. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…In the present study, RETTS had a sensitivity of 28% and a specificity 95% in cohort A and a sensitivity of 57% and specificity of 51% among infected patients in cohort B. A study of RETTS' association with the final hospital diagnosis in children demonstrated sepsis to be the most frequent inappropriately classified, time-dependant condition [22].…”
Section: Discussionmentioning
confidence: 42%
“…In the present study, RETTS had a sensitivity of 28% and a specificity 95% in cohort A and a sensitivity of 57% and specificity of 51% among infected patients in cohort B. A study of RETTS' association with the final hospital diagnosis in children demonstrated sepsis to be the most frequent inappropriately classified, time-dependant condition [22].…”
Section: Discussionmentioning
confidence: 42%
“…Adherence to guidelines in the context of EMS has been shown to be moderate. With adherence to clinical guidelines between 8 and 95%, among which monitoring recommendations are obeyed more frequently than treatment recommendations [36,37]. The adherence issues could relate to the formats of the guidelines, which make them difficult to use in a prehospital setting [24,36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is vital to encourage EMS providers to comprehensively examine the infant regardless of the possibly transient symptoms described by the caregivers. Indeed, even though EMS personnel did study vital signs more often than in the previously reported studies [ 13 , 24 , 33 ]; only heart rate, temperature and peripheral oxygen saturation reached over 50% coverage.…”
Section: Discussionmentioning
confidence: 78%
“…The complaints leading to EMS contacts were different in infants, as compared to those reported in the overall pediatric population [ 15 , 24 ]. Whereas dyspnea is among the leading causes for EMS contacts in children overall, infants had additional frequent EMS contacts due to choking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation